Sistem Pendukung Keputusan Dalam Menentukan Aparatur Sipil Negara Terbaik Pada Kantor Camat Siantar Utara Dengan Metode ELECTRE - Notryady Purba; Dedy Hartama; Jalaluddin J; Solikhun S; Fitri Anggraini (LPPM STIKOM Tunas Bangsa, 2020)
Siantar Utara District Office is one of the sub-districts in the Pematangsiantar city, North Sumatra Province. Through this sub-district office, residents can take care of various forms of licensing. At the subdistrict office also routinely held awards to employees which are held every three months which were previously counted on the excel application. The calculation process determines the best employee that the writer does, namely with the Excel application and uses the web-based ELECTRE method. Based on the final results obtained from the calculation results in both the excel application and the web-based application, alternative A1 with Ekl = 4 value, alternative A2 with Ekl = 4 value, alternative A3 with Ekl = 0 value, alternative A4 with Ekl = 2 value , alternative A5 with the value Ek = 2 From this decision support system, the final result is obtained with alternative A1 with the value Ekl = 4 as the best employee.